Answer:
B) [tex]r=\frac{\sqrt{Gm_{1}m_{2}F} }{F}[/tex]
Step-by-step explanation:
Newton's law of universal gravitation can be represented through the following expression.
[tex]F=G\frac{m_{1}m_{2}}{r^{2} }[/tex]
where,
F is the force between two objects
G is the constant of gravitation
m₁ is the mass of the first object
m₂ is the mass of the second object
r is the distance between the objects
We can solve this equation for "r".
[tex]F=G\frac{m_{1}m_{2}}{r^{2} }\\r^{2} =\frac{Gm_{1}m_{2}}{F} \\r=\sqrt{\frac{Gm_{1}m_{2}}{F}}\\r=\sqrt{\frac{Gm_{1}m_{2}F}{F^{2} }}\\r=\frac{\sqrt{Gm_{1}m_{2}F} }{F}[/tex]